1992
DOI: 10.1029/92jd01050
|View full text |Cite
|
Sign up to set email alerts
|

Water vapor column abundance retrievals during FIFE

Abstract: A variation of the modified Langley plot algorithm is reported here and applied to the retrieval of atmospheric water column abundance from a filtered sunphotometer. In this new methodology an absorption data base (LOWTRAN 7) is used to compute a water abundance versus transmittance curve of growth, rather than the square‐root dependence previously assumed. Validation of the technique is provided from an uncertainty analysis, and plans to further validate using Fourier transform spectrometers are detailed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(117 citation statements)
references
References 14 publications
0
111
0
4
Order By: Relevance
“…Using a power law parameterisation, a conversion of the slant optical depth to the slant IWV can be obtained (e.g. Bruegge et al, 1992;Schmid et al, 2001). Uncertainties in this parameterisation and the Langley plot regression (due to variable atmospheric water vapour amounts) as well as deficits in the filter characterisation are the leading error sources.…”
Section: Cimel Sun Photometermentioning
confidence: 99%
“…Using a power law parameterisation, a conversion of the slant optical depth to the slant IWV can be obtained (e.g. Bruegge et al, 1992;Schmid et al, 2001). Uncertainties in this parameterisation and the Langley plot regression (due to variable atmospheric water vapour amounts) as well as deficits in the filter characterisation are the leading error sources.…”
Section: Cimel Sun Photometermentioning
confidence: 99%
“…They found that the mixing ratio mean values for clear-sky days in the 1989 rainy season vary 30% during 9:00 -12:00 local time, and 40% in 12:00 -15:00. Bruegge et al (1992) reported that water vapor column abundances retrieved from the Airborne Visible Infrared Imaging Spectrometer (AVIRIS) data during the First ISLSCP Field Experiment (FIFE) over the Konza Prairie, Kansas, on August 31, 1990, indicated that the spatial variability over scales associated with surface topography and the underlying vegetation may be greater than 10%.…”
Section: Heritage For Lst Remote Sensingmentioning
confidence: 99%
“…At Izaña, we determine the water vapour columns by the modified Langley plot method. Therefore, the relation between the slant optical depth and the water vapour slant column amounts is approximated by a power law parameterisation (e.g., Bruegge et al, 1992;Schmid et al, 2001). Uncertainties in this parameterisation and the Langley regression (due to variable atmospheric water vapour amounts) as well as deficits in the filter characterisation are the leading error sources.…”
Section: Cimel Sunphotometermentioning
confidence: 99%